2021
DOI: 10.1051/0004-6361/202140969
|View full text |Cite
|
Sign up to set email alerts
|

First dust measurements with the Solar Orbiter Radio and Plasma Wave instrument

Abstract: Context. Impacts of dust grains on spacecraft are known to produce typical impulsive signals in the voltage waveform recorded at the terminals of electric antennas. Such signals (as may be expected) are routinely detected by the Time Domain Sampler (TDS) system of the Radio and Plasma Waves (RPW) instrument on board Solar Orbiter. Aims. We investigate the capabilities of RPW in terms of interplanetary dust studies and present the first analysis of dust impacts recorded by this instrument. Our purpose is to cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…The dust production was modeled by collisional fragmentation near the Sun and the dust trajectories were calculated with included radiation pressure and Lorentz force terms. Mann and Czechowski (2021) showed that the observed impact rates largely agree with the model calculations for dust > 100 nm and proposed that the differences may be explained by the influence of smaller particles and of other dust components, such as dust in bound orbits and interstellar dust.…”
Section: Exploration Of the Inner Solar Systemsupporting
confidence: 61%
See 3 more Smart Citations
“…The dust production was modeled by collisional fragmentation near the Sun and the dust trajectories were calculated with included radiation pressure and Lorentz force terms. Mann and Czechowski (2021) showed that the observed impact rates largely agree with the model calculations for dust > 100 nm and proposed that the differences may be explained by the influence of smaller particles and of other dust components, such as dust in bound orbits and interstellar dust.…”
Section: Exploration Of the Inner Solar Systemsupporting
confidence: 61%
“…Systematic studies of the dust flux near 1 AU are conducted with the Solar Terrestrial Relations Observatory (STEREO) (Zaslavsky et al, 2012) and Wind (Malaspina et al, 2014). The first analyses show that a large fraction of the observed dust particles are repelled from the Sun, i.e., the dust particles are in unbound orbits (Zaslavsky et al, 2021;Szalay et al, 2020;Malaspina et al, 2020). Mann and Czechowski (2021) used model calculations to explain the impact rates observed by the Parker Solar Probe.…”
Section: Exploration Of the Inner Solar Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…For particles orbiting at Keplerian speeds, we can assume a typical impact velocity of 30 km.s −1 ; the obtained mass range is then 20 − 340 × 10 −17 kg, which corresponds to the size interval 2 -5 µm (we assume a mass density ρ = 2.5 g.cm −3 ). On the other hand, it has appeared that the fluxes observed on several spacecraft, including STEREO (Zaslavsky et al 2012), but also Parker Solar Probe (Pusack et al 2021) and Solar Orbiter (Zaslavsky et al 2021), are dominated by impacts from a population of dust particles produced close to the Sun and pushed away along hyperbolic orbits by the radiation pressure, the β meteoroids. The velocity of these particles at 1 AU depends quite importantly on their origin and composition, through the value of the β parameter equal to the ratio of the radiation pressure force to the gravitational force on the dust grain.…”
Section: Electron Collectionmentioning
confidence: 99%